Comparison of the Effectiveness of Positive Thinking Training and Emotional Self-Regulation on Parenting Stress and Distress Tolerance in Mothers of Children with Autism Spectrum Disorder - Zaghian , Mahshid; Sharifi, Tayebeh; Ghasemi Pirbalouti , Mohammad (Mental Health and Lifestyle Journal, 2025)
The present study aimed to compare the effectiveness of positive thinking training and emotional self-regulation on parenting stress and distress tolerance in mothers of children with autism spectrum disorder. This research employed a quasi-experimental design with a pretest–posttest structure, including a control group and a two-month follow-up. The statistical population consisted of mothers of children with autism spectrum disorder in Isfahan during 2024–2025, from which 52 mothers were purposively selected and then randomly assigned to two experimental groups and one control group. The research instruments included the Parenting Stress Index (PSI; Abidin, 1995) and the Distress Tolerance Scale (DTS; Simons & Gaher, 2005). Both experimental groups received eight 90-minute sessions of positive thinking training and emotional self-regulation. Data were analyzed using repeated measures analysis of variance and Bonferroni post hoc tests. The results indicated that both positive thinking and emotional self-regulation training had a significant effect on parenting stress and distress tolerance (p < .001). The effectiveness of both interventions was maintained at the two-month follow-up. Furthermore, emotional self-regulation training was more effective than positive thinking training in reducing parenting stress and increasing distress tolerance (p < .001). The findings suggest that emotional self-regulation training should be prioritized over positive thinking training by therapists to improve parenting stress and distress tolerance in mothers of children with autism spectrum disorder.